Permanently polluted paradise? Gender inequality, care work, and community acts to waste problems in West Nusa Tenggara, Indonesia - Pakasi, Diana Teresa; Purnamasari, Marini (Universitas Trunojoyo Madura, 2024)
This article addresses the complex challenges of waste management on small islands in Indonesia, focusing on the impact of tourism and community response, particularly from a feminist political ecology (FPE) perspective. It argues that the current neoliberal and technocratic approaches to waste management are insufficient and often perpetuate gender inequalities. It calls for more inclusive and equitable waste management policies that recognize the contributions of all community members, particularly women. The research underscores the need for a gender equitable approach to environmental governance to achieve sustainable waste management and environmental justice. The research employed focused ethnography in North Lombok Regency, involving indepth interviews and focus group discussions. Our research found that while government efforts primarily focus on maintaining cleanliness for tourism, these initiatives often neglect inequalities in waste management strategies. Women play a crucial role in these grassroots initiatives, performing unpaid care work to manage waste, but face significant health risks and receive little recognition or support. The study recommends a shift from a tourismcentric approach to a community-centered model that invests in sustainable, long-term solutions prioritizing local needs, environmental health, and the empowerment of women, addressing environmental justice issues linked to tourism and waste accumulation.